Validity and Practicality Test of STEAM-Based E-Booklet on Food Microbiology Course - Rizka Ramadani Dalimunthe; Hasruddin Hasruddin; Mufti Sudibyo (Universitas Labuhanbatu, 2024)
The learning process in food microbiology courses generally uses learning media in the form of powerpoint slides which are still general in nature and have not been able to mobilize students' critical thinking skills. As a result, the student's ability score obtained is in the low category. This study aims to determine the level of validity and practicality of STEAM-based E-booklet media. This type of research is research and development using the ADDIE development model which consists of five stages, but in this case it is carried out until the development stage. The validity test was carried out by giving validation sheets to six experts while the practicality test was carried out by giving questionnaire sheets to lecturers and students. The results of the validity test by material expert validators, media experts and learning design experts obtained an average percentage of 88% with a very valid category. Practicallity test by course lecturers obtained an average percentage of 88,5% and student assessment of 97%. The E-booklet can be used as a learning media for students